2010
DOI: 10.5152/akd.2010.131
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension related to pulmonary diseases or hypoxia and its treatment

Abstract: ÖZETPulmoner hipertansiyon, akciğer hastalıklarının ileri evrelerinde sıklıkla ortaya çıkar ve kötü prognoz göstergesidir. Daha önce sekonder pulmoner hipertansiyon olarak adlandırılan, akciğer hastalıklarına bağlı olarak ortaya çıkan pulmoner hipertansiyon, son dönemde yapılan pulmoner hipertansiyon sınıflamasında ayrı bir kategori olarak ele alınmıştır. Kronik obstrüktif akciğer hastalığı seyri sırasında saptanan pulmoner hipertansiyon, diğer akciğer hastalıkları seyrinde saptanan pulmoner hipertansiyona kıy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
1
0
0
Order By: Relevance
“…6 In interstitial lung diseases, pulmonary hypertension can develop without hypoxemia, but hypoxemia is frequently observed. 7 In our study, consistent with this information, the average PaO 2 was found to be 53 mmHg in the group with PH and 68 mmHg in the group without PH. Likewise, the average oxygen saturation was found to be 88% in the group with PH and 94% in the group without PH.…”
Section: Discussionsupporting
confidence: 91%
“…6 In interstitial lung diseases, pulmonary hypertension can develop without hypoxemia, but hypoxemia is frequently observed. 7 In our study, consistent with this information, the average PaO 2 was found to be 53 mmHg in the group with PH and 68 mmHg in the group without PH. Likewise, the average oxygen saturation was found to be 88% in the group with PH and 94% in the group without PH.…”
Section: Discussionsupporting
confidence: 91%